Frequency of Peripheral Intravenous Catheter Related Phlebitis and Related Risk Factors: A Prospective Study (Journal of Medicine, 2019)
Background: Peripheral Intravenous Catheterization (PIVC) related complication is a common and significant problem in clinical practices. The aim of the study was to see the pattern of complication developed by PIVC and to find out the associated risk factors.Materials & methods: A prospective study was conducted amongst 300 patients and 420 PIVCs were observed.Results: 76 (18.09%) patients developed phlebitis and among the phlebitis patients 55.26% were grade 2 and 22.37% grade 3. Hypertonic fluid infusion and some antibiotics were found as risk factors for phlebitis. Amongst the antibiotics flucloxacilin (60%), amikacin (50%), amoxicillin + clavulanic acid were most common antibiotics responsible for development of phlebitis.Conclusions: Catheterization site and use of antibiotics and potassium chloride with associated co-morbidities are predisposing factors for phlebitis. Better insertion technique may be sought to lower the incidence of PIVC related complications.J MEDICINE JUL 2019; 20 (1) : 29-33